FRI0733-HPR The educational needs of patients with undifferentiated spondyloarthritis. (15th June 2017) - Bremander, A; Haglund, E; Bergman, S; Ndosi, M
Abstract : Background: The educational needs of people with undifferentiated spondyloarthritis (USpA) have not been well studied. The educational needs assessment tool (ENAT) has been translated into Swedish and validated in other rheumatic diseases but not USpA. 1 Objectives: To validate the educational needs assessment tool (ENAT) in people with USpA and use it to study their educational needs. Methods: A cross-sectional study recruiting a random sample of patients with USpA from a hospital register. USpA was diagnosed according to the International Classification of Disease, ICD-10 (M46.0, M46.1, M46.8, and M46.9). 1 The study was approved by the Regional Ethics Board and all included patients signed an informed consent. We used a postal survey to collect data on disease activity (BASDAI) and educational needs (Swedish version of the ENAT). 2 The data was then utilized to assess the construct validity, internal consistency, unidimensionality and response bias of the ENAT using Rash analysis. Given fit to the Rasch model, we transformed the ENAT ordinal scores into interval logit-based scores before deploying descriptive and inferential statistics. Total ENAT Score ranges between 0 (no needs) and 156 (the highest level of needs), and comprises seven subscales (pain 0–24, movement 0–20, feelings 0–16, disease 0–28, treatments 0–28, self-help 0–24 and support 0–16). Finally, we categorised the data by gender, age (median split) and disease activity (BASDAI split at 4) and assessed differences between patient subgroups using the student's t-test. Results: Complete responses were derived from 77 patients (48 women), mean (SD) age 50 (12) years, disease duration was 16 (11) years, BASDAI 4.9 (1.9) and BASFI 3.1 (2.3). When used as a 7-subscale questionnaire, the ENAT satisfied the requirements of Rasch model (c 2 =11.488; p=0.119) including strict unidimensionality. Overall, the mean (SD) ENAT scores for patients with USpA was 86 (32). Women reported higher needs than men in the domains of pain, mean (SD) 13.1 (6.8) vs. 10.1 (6.0), p=0.05; movement mean (SD) 13.0 (5.5) vs. 9.9 (5.7), p=0.02 and self-help, mean (SD) 17.0 (5.8) vs. 14.1 (5.0), p=0.03). Higher disease activity (BASDAI >4) was associated with higher educational needs, mean (SD) 92.6 (31.9) vs. 73.7 (29.4), p=0.02. There was no significant difference in educational needs between age groups. Conclusions: The Swedish ENAT has been validated in USpA thus enabling an accurate estimation of the educational needs of people with USpA in Sweden. Our data suggest that women and patients with higher disease activity are likely to have high levels of educational needs and these groups should be targeted in educational interventions for people with USpA. References: Classification of diseases, WHO, http://www.who.int/classifications/icd/en/ acessed 170103. Ndosi M, Bremander A, Hamnes B, et al. Validation of the Educational Needs Assessment Tool as a Generic Instrument for Rheumatic Diseases in 7 European Countries. Ann Rheum Dis 2014;73:2122–2129. Disclosure of Interest: None declared